The Clinical and Radiologic Features of Patients with Myelin Oligodendrocyte Glycoprotein (MOG) Antibody-Associated Disease (MOGAD) in the City of Sakarya, Türkiye - Saadet Sayan; Esen Çiçekli; Onur Taydaş; Mohammadreza Yousefi; Tansu Doran; Dilcan Kotan (Gazi Medical Journal)
Objective: The study aims to share our knowledge on myelin oligodendrocyte glycoprotein antibody (anti-MOG) seropositivity in patients with demyelinating diseases, focusing on their clinical, serologic, and radiologic characteristics, as well as treatment options for MOG associated disease (MOGAD) cases. Methods: This retrospective study included 332 of 450 demyelinating disease cases, aged 18 to 65 years, who were referred to our clinic from 2017 to 2023 with clinical and/or radiological signs of demyelination, followed by testing for the anti-MOG antibody. We applied the revised 2017 McDonald criteria and the 2023 MOGAD diagnostic criteria to those who tested positive for anti-MOG. Cases of anti-MOG seronegative multiple sclerosis (MS) and non-MOGAD were excluded. We detailed the clinical, serologic, and radiologic characteristics and treatment protocols of anti-MOG-positive/low-positive cases. Results: Among the cases, 16 were clear/low anti-MOG seropositive; of these, 10 were diagnosed with MOGAD, three were MS associated with anti-MOG seropositivity, and three were considered possible MOGAD and followed up. Four MOGAD cases (40%) were double positive for anti-MOG and oligoclonal bands. Three MOGAD cases also had autoimmune diseases. Rare clinical presentations included sixth cranial nerve palsy, tetraparesis secondary to acute disseminated encephalomyelitis, wall-eyed bilateral internuclear ophthalmoplegia and progressive transverse myelitis in adulthood. A total of 300 cases were diagnosed with MS, and 1% of these cases were anti-MOG with low levels of seropositivity. Conclusion: The pathogenesis, treatment, and prognosis of MOGAD differ from those of other demyelinating diseases. We aim to highlight the importance of recognizing MOGAD due to its potential association with autoimmune diseases, progressive nature, and dual seropositivity. Thus, it should be considered for its unique clinical and radiologic features.